Is the Phenomena of the Increase in Restaurants and Cafes in Lumajang is Directly Compared to Restaurant Tax Acquisition? - Kartika Ayu Kinanti; Moh. Hudi Setyobakti; Yulian Ade Chandra (Innovation Business Management and Accounting Journal, 2023)
This study aims to identify the extent to which the phenomenon of increasing restaurants and cafes in Lumajang has an impact on restaurant tax revenues. This research is a survey research with an interview method conducted with BPRD Lumajang and Restaurant/Cafe Owners who will be used as research samples where information or data is collected in a short time with several stages, namely determining interview questions, then the collected data will be identified and analyzed real-time. time. This research was carried out as an effort to optimize regional income through the local tax sector. The results of this study can be used as one illustration that in fact Lumajang still needs local tax socialization because the level of understanding and knowledge is lacking resulting in several potential taxes that should be able to increase regional income never reporting their tax obligations.